2022
DOI: 10.3389/fgene.2022.868717
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Liver and Muscle Tissues of Dorper and Small-Tailed Han Sheep

Abstract: It is well known that Dorper (DP) is a full-bodied, fast-growing and high dressing percentage breed, while the production performance of Small-tailed Han sheep (STH) is not so excellent, in contrast to DP. Therefore, in this study, a comparative transcriptomic analysis of liver and muscle tissues from DP and STH breeds was carried out to find differentially expressed genes (DEGs) that affect their growth and meat quality traits. The results showed that the total number of DEGs was 2,188 in the two tissues. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…WC populations are well known for their juiciness and for the flavour of their meat, and the SNPs identified in this study may help explain the genetic mechanisms underlying these favorable qualities. We also found that the SNPs identified in WC populations were related to developmental growth, which has been hypothesized to be involved in the growth and development of muscles (Peng et al, 2022). In addition, the GO terms of GO:0001525 – angiogenesis and GO:0005524 – ATP binding found in WC populations have been reported to be associated with the tolerance of ultraviolet radiation.…”
Section: Discussionsupporting
confidence: 56%
“…WC populations are well known for their juiciness and for the flavour of their meat, and the SNPs identified in this study may help explain the genetic mechanisms underlying these favorable qualities. We also found that the SNPs identified in WC populations were related to developmental growth, which has been hypothesized to be involved in the growth and development of muscles (Peng et al, 2022). In addition, the GO terms of GO:0001525 – angiogenesis and GO:0005524 – ATP binding found in WC populations have been reported to be associated with the tolerance of ultraviolet radiation.…”
Section: Discussionsupporting
confidence: 56%
“…Peng, et al (2022) found that 2188 DEGs were markedly up or downregulated between muscle and liver. There were 950,160 upregulated and 100,771 downregulated genes in the liver and muscle, respectively [ 23 ]. In the current study, 1346 genes were found to be differentially expressed in the subcutaneous fat of sheep fed different levels of wheat diets of Tibetan sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that the FABP3 gene is involved in muscle development and meat marbling [29,30]. FABP3 had been identified as a positive effect on the intramuscular fat content or fat deposition in the muscle of pigs or sheep [31][32][33]. The evidence including the validation results of RT-qPCR indicated a high correlation between this gene and the growth and meat production performance phenotypes of the goat population, suggesting that this FABP3 as an important candidate gene for grow period of our crossbred Chongming white goat population.…”
Section: Discussionmentioning
confidence: 99%